Tyrosine kinases: multifaceted receptors at the intersection of several neurodegenerative disease-associated processes - Stevenson, Max; Algarzae, Norah K.; Moussa, Charbel (Frontiers in Dementia, 2024)
Tyrosine kinases (TKs) are catalytic enzymes activated by auto-phosphorylation that function by phosphorylating tyrosine residues on downstream substrates. Tyrosine kinase inhibitors (TKIs) have been heavily exploited as cancer therapeutics, primarily due to their role in autophagy, blood vessel remodeling and inflammation. This suggests tyrosine kinase inhibition as an appealing therapeutic target for exploiting convergent mechanisms across several neurodegenerative disease (NDD) pathologies. The overlapping mechanisms of action between neurodegeneration and cancer suggest that TKIs may play a pivotal role in attenuating neurodegenerative processes, including degradation of misfolded or toxic proteins, reduction of inflammation and prevention of fibrotic events of blood vessels in the brain. In this review, we will discuss the distinct roles that select TKs have been shown to play in various disease-associated processes, as well as identify TKs that have been explored as targets for therapeutic intervention and associated pharmacological agents being investigated as treatments for NDDs.